Capital Market Failure, Adverse Selection and Equity Financing of Higher Education - Bas Jacobs; Sweder J.G. van Wijnbergen (Tinbergen Institute, 2005)
We apply theories of capital market failure to ana1yzeoptima1 financing of risky higher education. In the market solution,students can only finance their education through debt. There isunderinvestment in human capita1, because some students with socia1lyprofitable investments in human capita1 will not invest in educationdue to adverse selection problems in debt markets and becauseinsurance markets for human capita1 related risk are absent. Lega1limitations on the use of human capita1 in financia1 contracts cause thisunderinvestment; without them private markets would optima1lyfinance these risky investments through equity rather than debt andsupply income insurance. The government, however, can circumventthis problem and implement equity and insurance contracts through thetax system using a graduate tax. This paper shows that public equityfinancing of education coupled to provision of some income insuranceis the optimal way to finance education when private markets fail dueto adverse selection. We show that education subsidies to restoremarket inefficiencies are sub-optimal.
Keywords: H21; H24; H52; H81; I22; I28; J24; 330; human capital; capital market imperfections; credit rationing; financing risk investment; optimal education finance; graduate taxes; education subsidies; Bildungsinvestition; Studium; Studienfinanzierung; Bildungsfinanzierung; Kreditrationierung; Unvollkommener Markt; Finanzmarkt; Humankapital